Assessment of complications following use of pneumatic tourniquet for elective orthopedic procedures at National Orthopedic Hospital, Enugu - Ekwunife, Remigius T.; Iyidobi, Emmanuel C.; Enweani, Ugochukwu M.; Nwadinigwe, Cajetan U.; Okwesili, Charles I.; Ekwedigwe, Henry C.; Agbo, Emmanuel O. (International Journal of Research in Orthopaedics, 2019)
Background: A pneumatic tourniquet is a constricting or compressing device with an inflatable cuff used to control venous or arterial circulation to an extremity for a period of time. Tourniquet safety is related to the cuff pressure and duration of application. The objective of this study was to determine the common complications that follow the use of pneumatic tourniquet in elective orthopaedic surgical procedures at National Orthopaedic Hospital Enugu. Methods: This was a prospective study over 18 month period (June 2014 – November 2015) at National Orthopaedic Hospital, Enugu. Following ethical approval and written informed consent, patients who met the inclusion criteria were consecutively recruited. The study was conducted using the ‘intelligent pneumatic tourniquet’ with single bladder reusable cylindrical cuff. The cuff pressure was determined in each case by addition of 100mmHg to the baseline systolic BP for the upper limbs and 150 mmHg to the baseline systolic BP for the lower limbs. The data collected included patients’ demographics, cuff pressure, cuff location, tourniquet duration and complication encountered among other parameters. Results: A total of 160 procedures in 152 patients were included and analyzed using SPSS version 20.0. The prevalence rate of 1.9% for nerve palsy, 1.3% for tourniquet pain, 1.9% for surgical site infection and 5.6% for pressure sore were found in the study. No other complication was encountered. Conclusions: From the results of this study, it is concluded that the use of pneumatic tourniquet under the prescribed conditions is associated with low prevalence of complications.